2022
DOI: 10.3390/ijerph19063147
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Conservation in Macao SAR, China: The Role of Environmental Education among School Students

Abstract: Mangrove forests are one of the most ecologically valuable ecosystems in the world and provide a wide variety of ecosystem services to coastal communities, including cities. Macao, a highly urbanized coastal city located on the southern coast of China west of the Pearl River, is home to several species of mangroves with many associated flora and fauna. Mangrove forests in Macao are vulnerable to threats due to pressure from rapid and massive urban developments in the area, which led to mangrove loss in the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Environmental education and community engagement are crucial components for promoting the conservation and protection of mangroves. Recent research conducted in the city has demonstrated the effectiveness of environmental education activities in raising awareness and promoting conservation efforts for mangrove ecosystems [30]. The study reported consistently positive evaluations of mangrove-related environmental education programs, including exhibitions and field trips to coastal sites where mangroves grow.…”
Section: Mangrove Management and Protection Strategies In Macaomentioning
confidence: 81%
“…Environmental education and community engagement are crucial components for promoting the conservation and protection of mangroves. Recent research conducted in the city has demonstrated the effectiveness of environmental education activities in raising awareness and promoting conservation efforts for mangrove ecosystems [30]. The study reported consistently positive evaluations of mangrove-related environmental education programs, including exhibitions and field trips to coastal sites where mangroves grow.…”
Section: Mangrove Management and Protection Strategies In Macaomentioning
confidence: 81%
“…This supports the idea that direct exposure to unique environments, such as mangroves, can enhance students' understanding of ecological concepts and the value of biodiversity. Additionally, the significance of mangroves in educational settings is further supported by Tagulao et al (2022), who reported consistently positive evaluations of the impact of environmental education programs, emphasizing the role of such programs in raising awareness and influencing positive attitudes towards the preservation and conservation of marine ecosystems, including mangroves. These findings collectively highlight the educational and ecological significance of firsthand experiences in unique ecosystems, such as mangroves, in fostering a deeper understanding of ecological concepts and biodiversity appreciation among students.…”
Section: • Most Interesting Aspect Regarding Education In Mangrove Ec...mentioning
confidence: 93%